Adsorption of congo red using Mg/Al hydrotalcite - Muhammad Said; Neza Rahayu Palapa (Science and Technology Indonesia, 2017)
Polyoxometalate H4[α-SiW12O40].nH2O intercalated layered double hydroxide (1:1) was used as adsorbent colored-dye. Polyoxometalate H4[αSiW12O40].nH2O intercalated layered double hydroxide ratio (1:1) was applied as the adsorbent of Congo red-dye, and produce 51.38 (min-1) of the adsorption rate, for the largest of the adsorption capacity (b) 9.091 mol/g at 70°C, the largest adsorption energy 10.752 kJ/mol at 30°C. The value of the enthalpy (ΔH) and entropy (ΔS) decreased with increasing concentration of Congo red-dye. Effect adsorption of pH was show the optimal pH at 8 with the amount Congo red absorbed were 47.529 ppm. Keywords: Hydrotalcite, layered double hydroxide, polyoxometalate, intercalated, Congo red, adsorption